Cone-beam computed tomography in Endodontics: an exploratory research of the main clinical applications (Research, Society and Development, 2021)
This study revisited three oral radiology centers (ORC) and screened the main clinical indications that justified the request for cone-beam computed tomography (CBCT) examination in Endodontics. The databases of three ORCs were searched for requests of CBCT exams taken for Endodontic purposes over the last two years. The extracted data consisted of the total number of CBCT exams, the clinical indication in the endodontic field that justified the CBCT exam, the outcome of each exam (from the report of Oral Radiologists), and demographic data of the patients. From the total CBCT exams (n = 4,583), nearly 13% (n = 611) were taken for Endodontic purposes. Most of the clinical indications were related to root fractures (65%) and periapical lesions/disease (24.1%). Radiologists’ reports hypothesized more often toward periapical lesion/disease (70.5%), root fracture (51.4%) and accidents/complications (25.2%). Some clinical indications significantly varied based on age. In particular, post-traumatic imaging and the investigation of root resorption were more common in young patients, while the prevalence of exams for the investigation of pulpal calcifications and root fractures increased with age. More interestingly, there was a significant disagreement between the clinical indication that justified the CBCT examinations and the outcomes retrieved from radiologists’ reports (p < 0.005). This study illustrates the broad spectrum of CBCT applications for the diagnosis, treatment planning and follow-up in Endodontics. Attention is necessary to the disagreements between clinical indications and imaging outcomes, especially because certain conditions in the routine Endodontics are only visible with the aid of advanced tools.